Biomusic: The carrier - Batsis, Dimitri; Bitsikas, Xenophon; Georgaki, Anastasia; Evaggelou, Angelos; Tigas, Panagiotis (Technoetic Arts, 2012)
The present work investigates the concept of sound, in relation to the new means and sciences under different perspectives, ultimately providing an analysis of the newborn artistic movement of bioart. It deals with two parts. The first part of the study is based upon reference, investigating the interconnection between art and science. This mechanism is characterized by transformation processes in the interdisciplinary practices that are applied mainly by various artists and movements of the second post world war period. The expressive element seeks for an unworldly explanation through audio and visual conjunctions. This nature is obvious in Paul Klee’s reflections of musical elements in his paintings, Rimington’s attempts to marry audiovisual influences in his “colour organs”, the experimentations of composers like Xenakis and Stockhausen at various locations with light and color proves the continuous quest to render sound by the use of new means. Technology is a vital component of transformation as it enhances the syncretic creativity for various art domains like the ones that Fluxus deployed. Νam Jun Paik and Dick Higgins introduce radical techniques in their performances as they detach their selves from the parameters that define composition and use the mind and power of sentiment in order to identify reality aurally and optically. Towards the end of the 20th century we witness the appearance of new art forms like bioart. The human body, host of material and immaterial functions comes to the forefront of art practice. Its relation to elements such as oscillations and vibrations that express the energy flow are analyzed through the model of spiritualism that came from eastern thought. The notion of digital embodiment is presented as a reminder, highlighting the importance of technology in biotechnology and genetics. The second part of the study involves an experiment. This is how the concept of biomusic is applied with the use of ECG data from the MIT PhysioNet database. As sound penetrates the entire human body, it can be analyzed in all of its phasma. Using that information we attempt to translate/transform that biological sound phenomena into music. The sound produced by the elaboration of data which result from biological functions, can be described as Biomusic. It can be transformed into frequencies related to time and be expressed into music themes. Sonification plays an important role in this research as it constitutes a quick and precise rendering of the polymorphic information (in this case the E.C.G.) in musical notes. This modeling and musical attribution leads in two distinguished results each one of them concerning different clinical cases (all data belong to a normal heart function and a pathological one). The invention of this novel system is suggested for the scientific as well as for the music discipline. It has the ability to be implemented in an experimental form and obtain an educational character. The transformation process avoids compensation throughout the matching process in between E.C.G. functions and music, while focusing on the aesthetic factor at the same time. Sound meets art in the world of Biomusic as it takes shape through technology, constituting a new medium to further evolve the model of ‘’biology into art’’ transformation.